The Application of Al-Takyif in Islamic Research Methodology - Wan Mohd Khairul Firdaus, Wan Khairuldin; Daud, Ismail; Wan Khairul Aiman, Wan Mokhtar; Wan Nur Izzati, Wan Nor Anas; Abdul Hanis, Embong (2016)
Al-Takyif (adaptation) which is also known as al-takyif al-fiqhi is a new method to determine the current juristical issues related to Islam. Al-Takyif is adapted from al-Qiyas method in Usul al-Fiqh discussion. The study aims to examine al-Takyif’s applicability in Islamic Research Methodology. Therefore the library research and textual analysis are conducted. The objectives are compiled in two main parts. The first part explains the concept of al-takyif in determining the juristical issue. While the second part discusses the possibility of al-takyif application in Islamic Research Methodology. The findings show that method of al-takyif has a slight similarity with the literature review in Social Science Research Methodology. The findings also show the al-takyif method theoretically can be applied as a method in Islamic Research Methodology.